Resistivity measurements unveil microscopic properties of CrAs. (8th April 2019) - Nigro, Angela; Marra, Pasquale; Autieri, Carmine; Wu, Wei; Cheng, Jinguang; Luo, Jianlin; Noce, Canio
Abstract: We report resistivity measurements of a CrAs single crystal in a wide temperature range, with the specific aim to assess the applicability of the Bloch-Grüneisen formula for electron-phonon resistivity. We find that the resistance reaches a residual value at and its temperature dependence cannot be fitted only with a suitable Bloch-Grüneisen formula in the whole temperature range, even though we are able to calculate a well-defined transport Debye temperature. The observed temperature-dependent resistivity seems to suggest a non–phonon-mediated superconducting pairing, supporting a magnetic fluctuation mechanism as the likely glue for the superconducting coupling.